Unbalanced : the codependency of America and China - Roach, Stephen S. (Stephen Samuel), 1945- (Yale University Press, 2014)
"The modern-day Chinese and U.S. economies have been locked in an uncomfortable embrace since the late 1970s. Although the relationship was built on a set of mutual benefits, in recent years it has taken on the trappings of an unstable co-dependence. This insightful book lays bare the pitfalls of the current China-U.S. economic relationship, highlighting disputes over trade policies and intellectual property rights, sharp contrasts in leadership styles, the role of the Internet, and the political economy of social stability. Stephen Roach, a firsthand witness to the Asian financial crisis of the late 1990s and an economics expert who likely knows more about U.S.-China trade than any other Westerner, details how the two economies mirror one another. Co-dependency augments the tensions and suspicions between the two nations, but there is reason to hope for less antagonism and rivalry, the author maintains. In the wake of the 2008 financial crisis, both economies face structural changes that present opportunities for mutual benefit. Roach describes a way out of the escalating tensions of co-dependence and insists that the Next China offers much for the Next America--and vice versa"--